2010
DOI: 10.1002/ajhb.21092
|View full text |Cite
|
Sign up to set email alerts
|

Life history, immune function, and intestinal helminths: Trade‐offs among immunoglobulin E, C‐reactive protein, and growth in an Amazonian population

Abstract: Objectives Infection with helminths is associated with shifts in host immunity, including increased production of immunoglobulin E (IgE) and reduced inflammation. Given limited energy budgets, these shifts may involve changes in energy allocation toward competing demands. Here we test for potential trade-offs between growth, IgE, and the inflammatory marker C-reactive protein (CRP). Methods Dried blood spots and anthropometrics were collected from 162 Shuar forager-horticulturalists from a village in southea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 88 publications
(114 reference statements)
3
114
0
1
Order By: Relevance
“…Ages were determined by birthdates on government identification cards and the collection of extensive genealogical information, which included details about siblings and offspring, in order of birth. Overlapping genealogies were collected from multiple informants to cross-check information (Blackwell et al 2010). Pregnant women were not included in the study.…”
Section: Study Populationsmentioning
confidence: 99%
“…Ages were determined by birthdates on government identification cards and the collection of extensive genealogical information, which included details about siblings and offspring, in order of birth. Overlapping genealogies were collected from multiple informants to cross-check information (Blackwell et al 2010). Pregnant women were not included in the study.…”
Section: Study Populationsmentioning
confidence: 99%
“…It is also worth nothing that even in the absence of malnutrition and more virulent coinfecting species, coinfection in the Tsimane was associated with increased infection intensity. Previously, we have also shown that early and chronic elevated IgE-characteristic of endemic helminth exposure-is also associated with growth defi cits (Blackwell et al 2010 ). Thus, endemic exposure to multiple helminths may be a signifi cant cause of morbidity in the Tsimane.…”
Section: Helminth Coinfection and Infection Intensity Risk Among The mentioning
confidence: 84%
“…These results have implications for vaccination programs and the spread of epidemic diseases among the Tsimane and require further investigation. Other work has suggested that early and chronic elevated IgE, characteristic of endemic helminth exposure, is also associated with growth defi cits (Blackwell et al 2010 ). Therefore, helminth infection may still pose a substantial threat to health and well-being in the Tsimane and other nonindustrialized populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations